High‐Throughput DNA sequencing of ancient wood. Issue 5 (3rd March 2018) - Wagner, Stefanie; Lagane, Frédéric; Seguin‐Orlando, Andaine; Schubert, Mikkel; Leroy, Thibault; Guichoux, Erwan; Chancerel, Emilie; Bech‐Hebelstrup, Inger; Bernard, Vincent; Billard, Cyrille; Billaud, Yves; Bolliger, Matthias; et al.
Abstract: Reconstructing the colonization and demographic dynamics that gave rise to extant forests is essential to forecasts of forest responses to environmental changes. Classical approaches to map how population of trees changed through space and time largely rely on pollen distribution patterns, with only a limited number of studies exploiting DNA molecules preserved in wooden tree archaeological and subfossil remains. Here, we advance such analyses by applying high‐throughput (HTS) DNA sequencing to wood archaeological and subfossil material for the first time, using a comprehensive sample of 167 European white oak waterlogged remains spanning a large temporal (from 550 to 9, 800 years) and geographical range across Europe. The successful characterization of the endogenous DNA and exogenous microbial DNA of 140 ( 83%) samples helped the identification of environmental conditions favouring long‐term DNA preservation in wood remains, and started to unveil the first trends in the DNA decay process in wood material. Additionally, the maternally inherited chloroplast haplotypes of 21 samples from three periods of forest human‐induced use (Neolithic, Bronze Age and Middle Ages) were found to be consistent with those of modern populations growing in the same geographic areas. Our work paves the way for further studies aiming at using ancient DNA preserved in wood to reconstruct the micro‐evolutionary response of trees to climate change and human forest management.